Studies on Synthetic, Structural Characterization, Thermal, DNA Cleavage, Antimicrobial and Catalytic Activity of Tetradentate (N4) Schiff Base and Its Transition Transition Metal Complexes - Gandhi, S. Rajiv; Kumar, D. Sathis; Tajudeen, S. Syed; Sheriff, A.K. Ibrahim (Asian Journal of Chemistry, 2017)
A novel tetradentate chelate was synthesized by the condensation of cinnamaldehyde and triethylenetetramine. The chelate ligand was used to prepare mononuclear transition metal complexes of Mn(II), Fe(III), Co(II), Ni(II) and Cu(II) ions. They were charactertized by elemental analyses, conductivity studies, magenetic properties, infrared spectra, UV-visble spectra, 1H NMR and 13C NMR spectra, electron spin resonance spectra, mass spectra and thermogram studies. Their ligand field parameters and LFSE have also been determind. Kinetic studies on the hydrolysis of ethyl acetate have been studied using Co(II) and Ni(II) complexes as homogeneous catalysts and oxidation of pyrocatechol to o-quinone using Co(II), Ni(II) and Cu(II) complexes. The deoxyribonucleic acid cleavage activities of pUC19 DNA examined against chelate ligand and its metal complexes have been evaluated by agarose gel electrophoreises method in the presence of H2O2. The antimicrobial studies of Schiff base and its metal complexes were tested against the fungi Candida albicans and Aspergillus niger and bacteria Escherichia coli, Staphylococcus aureus and Bacillus cereus.